2009 International Workshop on Quality of Multimedia Experience 2009
DOI: 10.1109/qomex.2009.5246960
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced PESQ algorithm for objective assessment of speech quality at a continuous varying delay

Abstract: ITU-T P.862 -"Perceptual Evaluation of Speech Quality (PESQ)" is well known as an intrusive objective speech quality assessment method. Some reports have found that the PESQ time alignment mechanism fails to estimate delay where signals with high packet loss rate and dynamic time processing are present. A new time-alignment algorithm to improve the PESQ accuracy for time-scale modified voice transmission is suggested here. In the propose model, the time alignment of reference and degraded speech is estimated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Focusing on the frame-by-frame time alignment stage of PESQ, [15] noted that subjective scores may be poorly correlated as a result of errors in the objective quality scores caused by a few misaligned frames. Whereas, [16] discovered that PESQ time alignment failed to align continuous variable delays particularly with speech signals that have high packet loss rate and for which dynamic time processing is exhibited due to its piecewise constant delay estimation. The result of Malfait et al's work achieved a near-perfect delay profile in which for a misalignment of 10 ms, they obtained a correlation of 0.93 with the subjective score, for misalignment less than 5ms they obtained a correlation of 0.973, and have no significant improvement in the correlation coefficient for misalignment down to about 1 ms.…”
Section: Review Of Pesq's Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on the frame-by-frame time alignment stage of PESQ, [15] noted that subjective scores may be poorly correlated as a result of errors in the objective quality scores caused by a few misaligned frames. Whereas, [16] discovered that PESQ time alignment failed to align continuous variable delays particularly with speech signals that have high packet loss rate and for which dynamic time processing is exhibited due to its piecewise constant delay estimation. The result of Malfait et al's work achieved a near-perfect delay profile in which for a misalignment of 10 ms, they obtained a correlation of 0.93 with the subjective score, for misalignment less than 5ms they obtained a correlation of 0.973, and have no significant improvement in the correlation coefficient for misalignment down to about 1 ms.…”
Section: Review Of Pesq's Limitationsmentioning
confidence: 99%
“…They concluded that a time alignment of ±5 ms seemed good enough for correct assessment of time-warped signals. But [16] developed a new time-alignment algorithm that identifies both fix and variable delays in speech signals by using Dynamic Time Warping (DTW) in place of the utterances correlation and splitting methods used in the original PESQ algorithm.…”
Section: Review Of Pesq's Limitationsmentioning
confidence: 99%
“…It needs the reference signal and the degraded signal and its major steps are: level and time alignment, equalization, auditory transform, disturbance processing, cognitive modelling, and MOS (Mean Opinion Score) prediction. Other variations have also been defined as F-PESQ (Framed PESQ) [3] and E-PESQ (Enhanced PESQ) [14].…”
Section: Speech Quality Evaluationmentioning
confidence: 99%
“…The first is a time alignment stage that aligns the separated signal and reference signal. In the next stage a psychoacoustics model is used to calculate an auditory representation of the signals, followed by a cognitive model that calculates final score based on the differences between signals [7]. Formula (4) represents segmental version of SNR (SNRS), what is time domain measure.…”
Section: Measures For Intelligibility Assessmentmentioning
confidence: 99%